Temporal and spatio-temporal data mining - Hsu, Wynne 1966- (Gale virtual reference library, 2008)
Addresses different scenarios when finding complex relationships in spatio-temporal data by modeling them as graphs. It gives readers a comprehensive synopsis on two successful partition-based algorithms designed by the authors.